2004
DOI: 10.1155/s1110724304402034
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide as a Unique Bioactive Signaling Messenger in Physiology and Pathophysiology

Abstract: Nitric oxide (NO) is an intra- and extracellular messenger that mediates diverse signaling pathways in target cells and is known to play an important role in many physiological processes including neuronal signaling, immune response, inflammatory response, modulation of ion channels, phagocytic defense mechanism, penile erection, and cardiovascular homeostasis and its decompensation in atherogenesis. Recent studies have also revealed a role for NO as signaling molecule in plant, as it activates various defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 72 publications
3
137
0
5
Order By: Relevance
“…It is now well established that when the production of ROS exceeds the capacity of antioxidant defenses, oxidative stress will produce a harmful effect on the functional and structural integrity of biological tissues..The biological effects of ROS-mediated reactions are due to their direct interaction with cellular lipids, proteins and DNA (e.g., nicking, base-pair mutations, rearrangements, deletions, insertions and sequence amplification), causing cell damage and death. ROS also causes lipid peroxidation, which results in damage to the cell membrane and the membranes of cellular organelles (Tuteja et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…It is now well established that when the production of ROS exceeds the capacity of antioxidant defenses, oxidative stress will produce a harmful effect on the functional and structural integrity of biological tissues..The biological effects of ROS-mediated reactions are due to their direct interaction with cellular lipids, proteins and DNA (e.g., nicking, base-pair mutations, rearrangements, deletions, insertions and sequence amplification), causing cell damage and death. ROS also causes lipid peroxidation, which results in damage to the cell membrane and the membranes of cellular organelles (Tuteja et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…We found that NO production in C. albicans could be inhibited by the specific NOS inhibitor L-NAME, indicating that C. albicans may produce NO by a classic NOS mechanism [14,23]. We have carried out bioinformatic analysis on the C. albicans genome but failed to identify sequences that are homologous to known NOS (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, NO acts as a critical regulator in nervous, immune and cardiovascular systems [12], and an important mediator in certain pathophysiologic conditions [13]. NO in animals is synthesized by a family of enzymes, known as nitric oxide synthases (NOS), which catalyze the conversion of the amino acid L-arginine to NO and L-citrulline [14]. In plants, algae, and fungi, no true NOS homologs has yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…During the defence responses, NO may very rapidly react with O 2 -, provided there is sufficient NO to form peroxynitrite in the absence of enzymatic catalysis (Tuteja et al 2004;Saito et al 2006). An increase in peroxynitrite formation (9 h.p.i) in the resistant, with a transient peak induction (12 h.p.i; Fig.…”
Section: Discussionmentioning
confidence: 99%